A representação da experiência e identidade docente em um diário reflexivo: uma abordagem sistêmico-funcional - Dias, Sandra Maria Araújo (2010)
Based on the assumptions that texts represent and construe the world (FAIRCLOUGH, 1992), that identity construction occurs through individual and public forums‟ (TÁPIAS-OLIVEIRA, 2005), that ´located´ teacher development is essential in order to trigger a critical-reflective stance (FREEMAN, 1996; FREIRE, 1996; JOHNSON, 2006; REICHMANN, 2007a), this case study addresses a reflective journal produced by an EFL teacher the teacher-researcher herself over six months. In order to investigate teacher representations and discursive constructions about professional identity, this research follows an emic perspective (FREEMAN, 1998; GHEDIN & PIMENTA, 2002) and focuses on lexicogrammatical choices in the journal, grounded on Systemic-Functional Grammar, in special, the transitivity system (HALLIDAY, 1994; HALLIDAY e MATHIESSEN, 2004), and more specifically, in transitivity constructs such as Processes and mental projections. Systemic-Functional Grammar views language as a complex social semiotic system construing ideational, interpersonal and textual meanings (HALLIDAY, 1994). Results suggest that in terms of teacher representations, over time, there is an increase in relational and mental Processes, signaling characteristics related to teacher identity, students, the classes and the journal itself, as well as to reflective features of teaching practice. In terms of mental projections, they (re)constitute change in teacher positioning, suggesting new social roles adopted by the teacher. Highlighting the importance of the reflective journal as a literacy practice and as a literacy event, constituting a catalyzing genre‟ (SIGNORINI, 2006), it is relevant to underscore the importance of literacy practices in initial and continued language teacher development.